Development of a vaccine of cross-linked heat-stable and heat-labile enterotoxins that protects against Escherichia coli producing either enterotoxin. - Klipstein, F A (1982)
A vaccine of cross-linked heat-stable (ST) and heat-labile (LT) toxins that protects against heterologous serotypes of strains of Escherichia coli which produce either the LT or ST enterotoxin was developed by conjugating ST to LT by the carbodiimide reaction. Three interrelated factors were found to affect the composition and properties of the final conjugate: (i) the amount of carbodiimide added to the toxins, (ii) the initial ratio of ST to LT, and (iii) the duration of the conjugation reaction. Optimal conjugation conditions were identified as a carbodiimide-to-toxin ratio of 10:1 by weight, an initial molar ratio of ST to LT of 100:1, and a conjugation reaction time of 96 h. This approach yielded a conjugate that contained 96% by moles and 36% by weight pure ST, determined with radioiodinated pure ST, and 34% by weight semi-pure ST, determined by the Lowry protein method. The retained antigenicities of the conjugated toxins, as determined by enzyme-linked immunosorbent assays, was greater than or equal to 82%, and their toxicities, as determined by the Y1 adrenal cell assay for LT and by the suckling mouse assay for ST, were reduced to less than or equal to 0.15%. Immunization of rats with this cross-linked ST-LT vaccine provided strong protection against challenge with either the LT or the ST toxin or with viable heterologous strains which produce these toxins, either singly or together. These observations indicate that conjugation of ST to LT results in a unique new immunogen in that ST acquires immunogenicity as a function of the reaction, LT retains most of its antigenicity, and the toxic properties of each individual toxin are greatly reduced.